Tetanus: a case study - Pratiwi Hendro Putri (JOURNAL OF Medical Surgical Concerns, 2025)
Background: Tetanus is an acute bacterial infectious disease caused by clostridium tetani due to the exotoxin (tetanospasmin) it produces, affecting the nervous system causing muscles to become tense and contract with increased general stiffness and skeletal muscle spasms. Purpose: To discuss aspects of definition, epidemiology, etiology and risk factors, classification, pathophysiology, diagnosis, management, complications and prognosis of Generalized Tetanus. Method: Case report research, carried out at General Ahmadyani Metro Hospital, on 26 September – 03 October 2023. Research includes assessment, data analysis, action plan/plan of action (PoA), implementation, and evaluation. Data was collected through interviews and observations. Results: Motor function examination showed hypertonus and extremity muscle spasms. Meningeal stimulation examination revealed stiff neck (+). Laboratory examination showed a decrease in erythrocytes, hemoglobin and hematocrit and an increase in potassium. Conclusion: The diagnosis of tetanus can be made based on the history and physical examination. Culture examination of Clostridium tetani in wounds is only a support for the diagnosis. Keywords: Clostridium Tetani; Tetanus; Tetanospamin.   Pendahuluan: Tetanus adalah toksikosis akut yang disebabkan oleh neurotoksin yang dihasilkan oleh B. tetani dan ditandai dengan spasme otot yang periodik dan parah. Tetanus biasanya akut dan menyebabkan kelumpuhan spastik yang diinduksi tetanospasmin. Tetanospamin adalah racun saraf yang diproduksi oleh basil tetanus. Tujuan: Untuk membahas aspek definisi, epidemiologi, etiologi dan faktor resiko, klasifikasi, patofisiologi, diagnosis, tatalaksana, komplikasi dan prognosis Tetanus Generalisata. Metode: Penelitian case report, dilakukan di IGD RSUD Jendral Ahmadyani Metro, pada tanggal 26 September – 03 Oktober 2023. Penelitian meliputi  pengkajian,  analisis  data, rencana tindakan/plan of action (PoA), implementasi, dan evaluasi. Data dikumpulkan melalui wawancara, dan observasi.   Hasil: Pemeriksaan fungsi motorik terdapat hipertonus dan spasme otot extremitas. Pemeriksaan rangsang meningeal terdapat kaku kuduk (+). Pada pemeriksaan laboratorium menunjukkan penurunan pada eritrosit, hemoglobin dan hematokrit serta didapatkan peningkatan pada kalium. Simpulan: Diagnosis tetanus dapat ditegakkan berdasarkan anamnesis dan pemeriksaan fisik. Pemeriksaan kultur dari Clostridium tetani pada luka, hanya merupakan penunjang diagnosis. Kata Kunci: Clostridium Tetani; Tetanus; Tetanospamin.